THE INVOLVEMENT OF LIPIDS IN IMMUNE SYSTEM REGULATION: A MINI-REVIEW - Kurnia Putri Utami; Widya Wasityastuti; Marsetyawan HNE Soesatyo (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
An immune system recognizes and responds to antigens entering the body. Maintaining these roles, components of the immune system need energy obtained from nutrients such as carbohydrates, proteins, and lipids. This study reviews and discusses roles of lipids, particularly fatty acids, in regulations of the immune system. This study was conducted by conducting a literature study on published research articles written in English. The articles were obtained from PubMed and Google Scholar by using search keywords: lipid, fatty acids, immune, regulation, inflammation, and response. Lipids are a group of biomolecule compounds composed of carbon, oxygen, and hydrogen, and they are classified into simple, compound and complex lipids. Fatty acids are compound lipids that act as a main fuel for metabolism, an essential component for all membranes, and a gene regulator. Fatty acids have a modulating effect on immune cells, such as: acting as a host defence, activating the immune system, interacting with nuclear transcription factors, playing roles in inflammatory responses, promoting apoptosis, as well as influencing lymphocyte proliferation, cytokine production, and Natural Killer (NK) cell activities. However, the modulation of the immune system by lipids is influenced by various factors such as concentration and types of fatty acids, types of immune cells, and species. This study is suggested to provide an overview of beneficial roles of lipids in maintaining immunity.